QOS-enabled networks : - Barreiros, Miguel (John Wiley & Sons Inc., 2016)
Written by two experts in the field who deal with QOS predicaments every day and now in this 2nd edition give special attention to the realm of Data Centers, QoS Enabled Networks:Tools and Foundations, 2nd Edition provides a lucid understanding of modern QOS theory mechanisms in packet networks and how to apply them in practice. This book is focuses on the tools and foundations of QoS providing the knowledge to understand what benefits QOS offers and what can be built on top of it.